Lembaga Independen Pengawas ASN: Langkah Maju Reformasi Atau Beban Baru Kelembagaan Negara - Intan Nur’Aini; Karmila Nuralifah Kadir; Nadyya Dwi Wulandari; Aqila Fayyaza Ghafur; Farel Ananda Rizqi (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
Constitutional Court Decision Number 121/PUU-XXII/2024, which eliminates the Civil Service Commission (KASN) and transfers its duties to the National Civil Service Agency (BKN) as the new institution responsible for supervising the merit system, has generated significant concerns regarding the autonomy and effectiveness of internal bodies that are often viewed as underperforming. Based on a normative analysis grounded in relevant legal principles and theoretical frameworks, this ruling is seen as creating a gap in the oversight mechanism intended to safeguard the neutrality and integrity of the state civil apparatus. The shift in authority also introduces the potential for overlapping responsibilities that conflict with the fundamental doctrine of checks and balances. Such structural inconsistencies may weaken the supervision of civil service behavior and reduce the accountability expected from government institutions. Ultimately, these issues risk diminishing public confidence in the state apparatus, as the absence of an independent oversight body can hinder efforts to ensure professionalism, fairness, and ethical conduct within the ASN system.